Epidemiological profile of patients with psoriasis - Cogo, Juliana; Santos , Diego Henrique Rudnick dos; Campos, Ana Sara Martins de; Souza , Giandra Azolini Fernandes de; Freitas, Rosinei de; Alexandre, Mônica Micheli; Pinc , Mariana Moraes; Donadel, Guilherme; Gonçalves , Daniela Dib; Alberton , Odair; Boleta-Ceranto, Daniela de Cássia Faglioni; Lourenço, Emerson Luiz Botelho; et al. (Seven Editora, 2024)
Psoriasis is a disease that affects 2 to 3% of the world’s population. It is a chronic, non-communicable, painful, and disabling disease for which there is no cure. Thus, this study aims to describe the epidemiological profile, quality of life, and pharmacotherapy of patients with psoriasis. For this, a descriptive and quantitative cross-sectional study was conducted using online questionnaires that were applied to patients with psoriasis. The questionnaire included questions about socio-demographic data (gender, color, schooling, marital status), quality of life with questions related to day-to-day actions and pharmacotherapy (name of the drug, adverse reactions). We interviewed 554 individuals with a mean age of 38.72 years, with predominance of females (82.2%), white (70.1%) and with complete higher education (39.4%). The main clinical manifestations reported were scaling, itching and redness in the lesion regions. An average of 14.88 were obtained to evaluate the quality of life by the dermatology life qualify methodology. This disease causes negative impacts on patients’ quality of life, mainly due to the development of other comorbidities (anxiety and depression); With this study, we confirm how psoriasis affects the quality of life of patients, since stigmatization of the individual in social environments and the adverse effects caused by drugs, in addition to promoting the appearance of other comorbidities. DOI:https://doi.org/10.56238/sevened2024.001-040